Respuesta :
Solve: 4x + 3 =2x +9
4x + 3 = 2x + 9
-2x -2x
2x + 3 = 9
-3 -3
2x = 6
2x/2 = 6/2
x = 3
Answer would be : x = 3
4x + 3 = 2x + 9
-2x -2x
2x + 3 = 9
-3 -3
2x = 6
2x/2 = 6/2
x = 3
Answer would be : x = 3
4x + 3 = 2x + 9
Start by subtracting 2x from both sides, which leaves you with...
2x + 3 = 9
Now that 'x' is moved to one side—in this case the left—start subtracting the '3' from both sides...
2x = 6
Now that 'x' is isolated, you can now solve...start by dividing both sides by 2.
2x/2 = 6/2
Your final answer should be...
x = 3
Start by subtracting 2x from both sides, which leaves you with...
2x + 3 = 9
Now that 'x' is moved to one side—in this case the left—start subtracting the '3' from both sides...
2x = 6
Now that 'x' is isolated, you can now solve...start by dividing both sides by 2.
2x/2 = 6/2
Your final answer should be...
x = 3